4, 4′-Dichlorodiphenyl diselenide reverses a depressive-like phenotype, modulates prefrontal cortical oxidative stress and dysregulated glutamatergic neurotransmission induced by subchronic dexamethasone exposure to mice. (September 2019) - Heck, Suélen Osório; Zborowski, Vanessa Angonesi; Quines, Caroline Brandão; Nogueira, Cristina Wayne
Abstract: Dexamethasone (DEX) is a synthetic agonist of glucocorticoid receptors that has been associated with neurotoxicity and neuropsychiatric diseases. (p-ClPhSe)2 is an organoselenium compound reported to have antioxidant, antidepressant-like, and neuroprotective actions. This study investigated whether antioxidant activity and modulation of the glutamatergic system contribute to the antidepressant-like effect of (p-ClPhSe)2 in mice subchronically exposed to DEX. Swiss mice received intraperitoneal injections of DEX (2 mg/kg) or saline (vehicle) once a day for 21 days. After, the mice received (p-ClPhSe)2 (1–10 mg/kg) or mineral oil (vehicle) by the intragastric route (i.g.) for 7 days. The mice exposed to DEX were treated with fluoxetine (20 mg/kg, i.g.) once a day for 7 days. 24 h after the last treatment, the animals performed the locomotor activity (LMA), tail suspension, and forced swimming tests. Ex vivo assays were performed in samples of prefrontal cortex (PFC). The results show that (p-ClPhSe)2 reversed depressive-like behavioral phenotype induced by DEX without affecting LMA. Further, (p-ClPhSe)2 at all doses reduced ROS levels and increased CAT activity in the PFC of DEX-exposed mice. The highest dose of (p-ClPhSe)2 was effective against the decrease of SOD activity in the PFC of mice exposed to DEX. (p-ClPhSe)2 increased the [ 3 H] glutamate uptake/release and decreased the Na + /K + -ATPase activity as well as the EAAT1 and NMDA R2A protein contents in the PFC of DEX-exposed mice. Regarding the NMDA R2B levels, there was no difference among experimental groups. In conclusion, this study reveals the effectiveness of (p-ClPhSe)2 in reversing the depressive-like phenotype of DEX-exposed mice. In addition, (p-ClPhSe)2 modulated oxidative stress and glutamate neurotransmission in the PFC of mice subchronically exposed to DEX. Graphical abstract: Image 10113 Highlights: (p-ClPhSe)2 reverses depressive-like behavioral phenotype induced by DEX in mice. (p-ClPhSe)2 has an antioxidant action in the PFC of mice exposed to DEX. (p-ClPhSe)2 modulates the glutamatergic system in the PFC of mice exposed to DEX.